Hidup Demi Eksistensi dan Validasi di Tengah Tren FOMO Sosial Media - Wahyu Trisno Aji; Meti Rosiana; Ahmad Arfandi Musida; Fitriati Wahyuni (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This article aims to explain the conditions of Gen Z in the blanket of rapid development of digitalization technology. This article uses a qualitative method with a literature study and a descriptive analytical approach. The results of the study indicate that the Fear of Missing Out (FOMO) phenomenon on social media reflects symptoms of deep anxiety experienced by modern society, especially Generation Z, due to the fear of being left behind by information or trends that are considered important. In a digital world full of endless information, individuals are encouraged to stay connected and consume content that is often irrelevant, creating the illusion of engagement and validation. This phenomenon creates a great irony, where social media, which should be a tool for communication and information, has instead become a space filled with social pressure, value gaps, and artificial scenarios. The impact of FOMO can be seen in psychological aspects, such as anxiety, depression, and low self-confidence; social, in the form of a decrease in the quality of direct relationships between individuals; and physical, such as lack of sleep and reduced physical activity. However, social media also offers positive opportunities, such as increased creativity, network expansion, and the opening of new opportunities, if used wisely. To overcome the negative impacts of FOMO, efforts are needed to limit the time spent using social media, change the mindset to be more reflective and productive, and engage in meaningful activities.